ANALYSIS OF THE SPATIAL VARIABILITY OF RESISTANCE TO SOIL PENETRATION AT DIFFERENT DEPTHS - Ferrari, J. M. S.; Gabriel, C. P. C.; Silva, T. B. G.; Mota, F. D.; Gabriel Filho, L. R. A.; Tanaka, E. M. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The compaction of the soil in sugarcane cultivated areas is very accentuated due to the intense use of machines and agricultural implements, it is one of the factors that cause serious restrictions to the root development of the plants. The objective of this work was to characterize the spatial variability of soil penetration resistance (SPR) of a reforested area after five years of sugar cane cultivation. The experiment was conducted in April 2015 at the Santa Martha Farm located in Espirito Santo do Turvo, SP. The SPR was collected by means of an electric penetrometer, in previously georeferenced points totaling 56 points, distributed in an irregular area. Geostatistics was used to analyze the spatial variations of SPR from five different soil depths (1, 10, 20, 30 and 40 cm). Soil moisture was collected only at central points. The semivariogram model that best fit the values ​​of SPR was spherical. This study resulted in high and moderate degrees of spatial dependence, in the profiles of 1, 10 and 20 cm, and pips effect in depths 30 and 40 cm. It was possible to evaluate the spatial variability of RSP by means of geostatistics, with the highest homogeneity in the 1, 10 and 20 cm profile.